An injectable, electrostatically interacting drug depot for the treatment of rheumatoid arthritis - Park, Ji Hoon; Park, Seung Hun; Lee, Hye Yun; Lee, Jin Woo; Lee, Bo Keun; Lee, Bun Yeoul; Kim, Jae Ho; Kim, Moon Suk (Biomaterials, 2018)
To the best of our knowledge, no studies have yet examined the electrostatic interaction of polyelectrolytes with electrolyte drugs for the treatment of rheumatoid arthritis (RA). Here, an injectable, electrostatically interacting drug depot is described. We prepared methoxy polyethylene glycol-b-poly(ε-caprolactone)-ran-poly(L-lactic acid) (MC) diblock copolymers with a carboxylic acid group (MC-C) at the pendant position. MC-C was polyelectrolytes that exhibited negative zeta potentials. Sulfasalazine [Sul(−)] and minocycline [Min(+)], electrolyte RA drugs, exhibited negative and positive zeta potentials, respectively. The electrolyte RA drugs were loaded into the polyelectrolyte MC-C solution to prepare injectable, electrostatically interacting depot formulations. The formulation with an attractive electrostatic interaction [Min(+)-MC-C] exhibited gradual release of Min(+) from the MC-C depot over an extended period and suppressed the growth of inflammatory RAW 264.7 cells without affecting synovial cells. Mature chondrocytes were observed after H&E and safranin O staining of the cartilage of Min(+)-MC-C intra-articularly injected RA-induced rats. In comparison with other formulations, Min(+)-MC-C induced the suppression of the expression of pro-inflammatory proteins TNF-α and IL-1β in the articular knee joint, which resulted in the amelioration of RA. In conclusion, an injectable, electrostatically interacting depot formulation administered through intra-articular injection successfully provided almost complete amelioration of RA.
Keywords: Carboxylic acid groups; Depot; Intra-articular injection; Methoxypolyethylene glycol; Negative zeta potentials; Poly (epsiloncaprolactone); Poly L lactic acid; Rheumatoid arthritis; Animals; Arthritis, Rheumatoid; Cartilage, Articular; Cell Survival; Drug Liberation; Inflammation; Injections; Interleukin-1beta; Male; Mice; Phase Transition; Polymers; Rats, Inbred Lew; RAW 264.7 Cells; Reproducibility of Results; Solutions; Static Electricity; Synovial Membrane; Temperature; Tumor Necrosis Factor-alpha; Viscosity; Depot; Electrostatic interaction; Intra-articular injection; Polyelectrolytes; Rheumatoid arthritis